2014
DOI: 10.1099/jmmcr.0.000001
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Shiga toxin 2e‐producing Escherichia coli and atypical enteropathogenic E. coli in an asymptomatic child

Abstract: Introduction:Escherichia coli causes gastroenteritis in humans and animals.Case presentation:In this study, both Shiga toxin-producing E. coli (STEC) and atypical enteropathogenic E. coli (EPEC) strains were identified in a stool sample from a healthy child, and they were serotyped as Shiga toxin-producing E. coli (STEC) ONT : H19 and atypical enteropathogenic E. coli (EPEC) O37 : H45.Conclusion:This is the first report, to our knowledge, of a concomitant presence of diarrhoeagenic E. coli (DEC) strains in an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Although Stx2e is a less common subtype in human STEC strains, studies have shown associations between Stx2e-STEC and severe symptoms such as HUS [16,37,38], and diarrhea [18,19]. Molecular characterization revealed that human-derived Stx2e-STEC strains in this study were diverse.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Although Stx2e is a less common subtype in human STEC strains, studies have shown associations between Stx2e-STEC and severe symptoms such as HUS [16,37,38], and diarrhea [18,19]. Molecular characterization revealed that human-derived Stx2e-STEC strains in this study were diverse.…”
Section: Discussionmentioning
confidence: 64%
“…Stx2e-STECs have also been found in environmental samples such as wastewater [15]. Although Stx2e-STEC is less frequently identified in humans, a few studies have indicated an association between Stx2e-STEC and human HUS [16], mild diarrhea, or asymptomatic cases [17][18][19], but the relationship between STEC isolates and human diseases has not been clearly delineated.…”
Section: Introductionmentioning
confidence: 99%